EFISIENSIEKONOMIRELATIF USAHATANI TEMBAKAU MENURUT SISTEM PENGUASAAN LAHAN SAW AH DI KABUPATEN TEMANGGUNG - Dewi Kusuma Wardani; Waridin Waridin (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
The research is aimed at analyzing and comparing the efficiency levels, in terms of technique, cost and economic of the owner farmers and non-owner (rent and sharecropping) farmers who cultivated tobacco farming in Temanggung district, Central Java. The result of research shows that the input variables, namely seed, fertilizer, pesticide, and manpower have influence on profit level of the farm. In addition, input variables for the owner farmers and non owner (rent and share cropping) farmers have not used optimally.